An interacting two-fluid scenario for dark energy in a Bianchi type-I cosmological model - Singh T.; Chaubey R. (My University, 2025)
We study the evolution of the dark energy parameter within a Bianchi type-I cosmological model filled with barotropic fluid and dark energy. The solutions have been obtained for power law and exponential forms of the expansion parameter (they correspond to a constant deceleration parameter in general relativity). After a long time, the models tend to be isotropic under certain conditions. © 2012 National Astronomical Observatories of Chinese Academy of Sciences and IOP Publishing Ltd.